Amelioration by chlorophytum borivilianum upon arsenic induced oxidative stress in Swiss albino mice - Sharma, Garima; Kumar, Madhu (International Journal of Pharmacology and Toxicology, 2014)
Background: Arsenic, a major water pollutant in India, produces toxic effects on male reproductive system due to oxidative stress. Arsenic contaminated drinking water causes several health problems such as Blackfoot disease, hypertension, diabetes mellitus, disturbances in the nervous system and cancers of liver, kidney, lung and bladder in humans. Aim: This study accessed the efficacy of Chlorophytum borivilianum in reducing arsenic-induced biochemical and nucleic acid damages in mice testis. Methods: A different group of adult Swiss albino mice was made such as control group, C. borivilianum group, sodium arsenite group and combination group. For antioxidant activity, ABTS radical cation decolorization assay was done. Body and testis weight, protein, sialic acid, ATPase activity, DNA and RNA content in the testis were also estimated. Results: Animals exposed to sodium arsenite at the dose of 4.0 mg/kg b.wt. showed significant decrease (p<0.001) in testicular protein, sialic acid, ATPase activity, DNA and RNA content indicate DNA damage and apoptosis whereas combination group showed a significant increase in all the parameters. Conclusion: The results thus led us to conclude that administration of C. borivilianum at the dose of 800 mg/kg b.wt. Significantly protects against arsenic-induced oxidative stress. Keywords: ABTS Assay; Atpase; DNA; Oxidative Stress; Protein; Sialic Acid.